2022
DOI: 10.1038/s41419-022-05446-9
|View full text |Cite
|
Sign up to set email alerts
|

p53 triggers mitochondrial apoptosis following DNA damage-dependent replication stress by the hepatotoxin methyleugenol

Abstract: Liver cancer is one of the most frequent tumor entities worldwide, which is causally linked to viral infection, fatty liver disease, life-style factors and food-borne carcinogens, particularly aflatoxins. Moreover, genotoxic plant toxins including phenylpropenes are suspected human liver carcinogens. The phenylpropene methyleugenol (ME) is a constituent of essential oils in many plants and occurs in herbal medicines, food, and cosmetics. Following its uptake, ME undergoes Cytochrome P450 (CYP) and sulfotransfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…Saponine (0.1%) served as positive control and solvent as negative control. Cell viability was determined as described previously (Carlsson et al 2022 ). After 24 h and 72 h, cells were washed with PBS and incubated for 1 h with DMEM low glucose (-FCS; -P/S) or William’s E Medium (1X) supplemented with 10% 440 µM Resazurin-NaCl-Pi-solution (0,1% dimethylformamide; 1.1 mM KH 2 PO 4 , 154 mM NaCl, 3.7 mM Na 2 HPO 4 ) at 37 °C in humidified atmosphere of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Saponine (0.1%) served as positive control and solvent as negative control. Cell viability was determined as described previously (Carlsson et al 2022 ). After 24 h and 72 h, cells were washed with PBS and incubated for 1 h with DMEM low glucose (-FCS; -P/S) or William’s E Medium (1X) supplemented with 10% 440 µM Resazurin-NaCl-Pi-solution (0,1% dimethylformamide; 1.1 mM KH 2 PO 4 , 154 mM NaCl, 3.7 mM Na 2 HPO 4 ) at 37 °C in humidified atmosphere of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…DSBs are the main causative factor for genome instability . Upon encountering DSBs in the DNA, the cells maintain the stability of the genome through a series of responses, including cell cycle arrest, DNA repair, and apoptosis. , Previous studies have shown that PARP1 inhibitors cause DSBs in BRCA-deficient tumor cells, thereby inducing apoptosis and cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…8 In a recent study, it was shown that ME caused DNA damage-dependent replication stress resulting in mitochondrial apoptosis via the p53-Bax pathway. 9 ME-derived DNA adducts, found in cell culture experiments, 10,11 were also detected in mice, 12−15 and, most importantly, in humans. 16−18 To be precise, the presence of DNA adducts, primarily N 2 -(methylisoeugenol-3′-yl)-2′-deoxyguanosine, was demonstrated in 150 out of 151 surgical human liver samples 16,17 and 10 out of 10 lung samples 18 investigated.…”
Section: ■ Introductionmentioning
confidence: 88%
“…Furthermore, ME increased the mutational burden in hepatocellular carcinomas of mice in a dose-dependent manner, leading to mutational signatures similar to those in human hepatocellular carcinomas with known exposure to the carcinogens aflatoxin or benzo­[ a ]­pyrene . In a recent study, it was shown that ME caused DNA damage-dependent replication stress resulting in mitochondrial apoptosis via the p53-Bax pathway …”
Section: Introductionmentioning
confidence: 92%